2011
DOI: 10.1093/mp/ssr028
|View full text |Cite
|
Sign up to set email alerts
|

Rice OsGL1-1 Is Involved in Leaf Cuticular Wax and Cuticle Membrane

Abstract: Cuticular wax forms a hydrophobic barrier on aerial plant organs; it plays an important role in protecting a plant from damage caused by many forms of environmental stress. In the present study, we characterized a rice leaf wax-deficient mutant osgl1-1 derived from a spontaneous mutation, which exhibited a wax-deficient and highly hydrophilic leaf phenotype. We cloned the OsGL1-1 gene by the map-based cloning method and performed a complementation test to confirm the function of the candidate gene. Molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 54 publications
2
73
0
3
Order By: Relevance
“…To test the hypothesis, we checked the wax status using Ox-WR1 and RI-WR1 plants, showing significant increase and decrease, respectively. These observations suggest that the regulation of OsWR1 in wax synthesis related genes and wax production possibly affects the water loss and drought tolerance in plants, consistent with the wax function in drought response (Aharoni et al 2004;Broun et al 2004;Islam et al 2009, Qin et al 2011Seo et al 2011). Therefore, data in the present report show that OsWR1 is, to our knowledge, the first example of an ERF transcriptional activator affecting the expression of wax synthesis related genes in rice.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…To test the hypothesis, we checked the wax status using Ox-WR1 and RI-WR1 plants, showing significant increase and decrease, respectively. These observations suggest that the regulation of OsWR1 in wax synthesis related genes and wax production possibly affects the water loss and drought tolerance in plants, consistent with the wax function in drought response (Aharoni et al 2004;Broun et al 2004;Islam et al 2009, Qin et al 2011Seo et al 2011). Therefore, data in the present report show that OsWR1 is, to our knowledge, the first example of an ERF transcriptional activator affecting the expression of wax synthesis related genes in rice.…”
Section: Discussionsupporting
confidence: 85%
“…The Arabidopsis genes, such as CER1 (McNevin et al 1993), CUT1/CER6 (Millar et al 1999), KCS1 (Todd et al 1999), FDH (Pruitt et al 2000), and the maize genes GL1 (Sturaro et al 2005) and GLOSSY2 (Tacke et al 1995) have been proposed or shown to encode enzymes or components of the secretory pathway (Millar et al 1999;Todd et al 1999;Chen et al 2003;Islam et al 2009;Qin et al 2011). Other genes, such as CER2 and CER3, encode regulatory proteins that might be involved in wax biosynthesis (Xia et al 1996;Rowland et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cuticle plays an important role in rice flower morphogenesis, anther and pollen development, pathogen resistance, and salt tolerance (Bird et al, 2007;Qin et al, 2011Qin et al, , 2013. However, our understanding of cuticle function in panicle development remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutants or transgenic lines with reduced levels of verylong-chain alkanes often display elevated rates of water loss (Vogg et al, 2004;Leide et al, 2007;Qin et al, 2011). Furthermore, enhancing the levels of these wax components can restrict water loss, leading to improved drought tolerance (Bourdenx et al, 2011;Seo et al, .…”
Section: A Role For Cd2 In Reducing Leaf Water Lossmentioning
confidence: 99%